Evidence for the Induction of Key Components of the NOTCH Signaling Pathway via Deltamethrin and Azamethiphos Treatment in the Sea Louse Caligus rogercresseyi - Boltaña, Sebastian (Int J Mol Sci, 2016)
The extensive use of organophosphates and pyrethroids in the aquaculture industry has negatively impacted parasite sensitivity to the delousing effects of these antiparasitics, especially among sea lice species. The NOTCH signaling pathway is a positive regulator of ABC transporter subfamily C expression and plays a key role in the generation and modulation of pesticide resistance. However, little is known about the molecular mechanisms behind pesticide resistance, partly due to the lack of genomic and molecular information on the processes involved in the resistance mechanism of sea lice. Next-generation sequencing technologies provide an opportunity for rapid and cost-effective generation of genome-scale data. The present study, through RNA-seq analysis, determined that the sea louse Caligus rogercresseyi (C. rogercresseyi) specifically responds to the delousing drugs azamethiphos and deltamethrin at the transcriptomic level by differentially activating mRNA of the NOTCH signaling pathway and of ABC genes. These results suggest that frequent antiparasitic application may increase the activity of inhibitory mRNA components, thereby promoting inhibitory NOTCH output and conditions for increased resistance to delousing drugs. Moreover, data analysis underscored that key functions of NOTCH/ABC components were regulated during distinct phases of the drug response, thus indicating resistance modifications in C. rogercresseyi resulting from the frequent use of organophosphates and pyrethroids.